Novel and simple method using cable ties to induce intestinal strangulation in a rat model (Faculty of Medicine Universitas Indonesia, 2022)
BACKGROUND The pathogenesis of intestinal fibrosis after strangulation in abdominal surgery is not fully understood. Developing an experimental and reliable method is needed to overcome this problem. This study aimed to develop an effective method for intestinal strangulation leading to fibrosis, which might induce intestinal obstruction. METHODS This study was conducted from 2018 to 2019 at the Department of Pharmacology, Faculty of Medicine, Universitas Indonesia. A total of 24 Sprague Dawley rats were used in this study. Artificial intestinal strangulation using cable ties made of durable plastic, which is generally used to ligate objects, was applied, and rats were further classified into control, 6-hour, and 24-hour strangulation groups. At the end of the study, the rats were sacrificed, intestinal tissues were collected, and histomorphological changes were observed using hematoxylin and eosin stain. Moreover, Masson’s trichome staining was used to assess collagen density. RESULTS Median collagen density score of the 24-hour strangulation group was higher than the control. A significant difference in collagen density was found between the submucosal layer of the 24-hour strangulation group and the control (45.4 [11.4] versus 32.4 [14.0], p<0.001) and between the mucosa of the 6- and 24-hour strangulation groups and the control (26.9 [17] versus 6.46 [4.3], p = 0.01 and 24.9 [8] versus 6.46 [4.3], p = 0.004, respectively). CONCLUSIONS The simple use of cable ties adequately promotes intestinal strangulation.